Students enjoyment and anxiety in reminiscing about mind-mapping use in the English writing class - Ariyanti, Ariyanti; Setiawan, Slamet; Munir, Ahmad (Studies in English Language and Education, 2023)
The present study examines students foreign language enjoyment and anxiety when reminiscing about the mind-mapping app in the English writing class. This research uses sequential explanatory mixed method to cover quantitative and qualitative elements of students emotions in foreign language writing. Foreign language enjoyment (FLE) and foreign language classroom anxiety (FLCA) questionnaires were distributed to 122 students at two universities in Indonesia, followed by interviewing some representative students. The findings revealed that students enjoyed the use of the mind-mapping app because they thought that they were free to design their own version of mind-mapping with interesting shapes and colours. However, indications of worrying about the mind mapping they made came from fear of being embarrassed in front of their friends. Additionally, the essence of competition also drove the students to be worried in the writing class. It made them feel that other friends had better mind maps. Second, even though having a group discussion in the writing class was interesting for the students, the fear of friends stealing ideas was detected. There was also an indication that the students were concerned about their achievement in writing class. It implies that teachers need to reminisce students ideas and not give negative comments in front of the class to avoid increasing students anxiety, but build up enjoyment instead to boost their devotion to the writing class.